Polycarbonate / polyethylene glycol terephthalate material and preparation method thereof

By using triphenylphosphinic acid itaconic anhydride as a modifier in polycarbonate/polyethylene terephthalate materials, the problem of material degradation and mechanical properties after the introduction of fillers is solved, and efficient flame retardant performance is achieved to meet the needs of new energy vehicles and other fields.

CN119552491AActive Publication Date: 2025-03-04WANHUA CHEMICAL (NINGBO) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411620238.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-04
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

In polycarbonate/polyethylene terephthalate materials, the introduction of fillers leads to material degradation and mechanical properties, and the flame retardant performance is insufficient, making it difficult to meet the needs of new energy vehicles and other fields.

Method used

Itaconic anhydride phosphate triphenylphosphinic acid is used as a modifier and mixed with PC/PET material. By combining the anhydride structure and chain extender components, the melt strength and viscoelasticity of the material are improved, and the flame retardant performance is improved through the phosphobenzene structure.

Benefits of technology

It effectively inhibits the degradation of the material system, improves impact performance and modulus, and achieves efficient flame retardant effects, meeting the application needs of the automotive industry and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133251240000021
    Figure BDA0005133251240000021
  • Figure HDA0005133251250000011
    Figure HDA0005133251250000011
Patent Text Reader

Abstract

The invention provides a polycarbonate / polyethylene glycol terephthalate material and a preparation method thereof. The material comprises the following raw materials: PC, PET, a triphenylphosphinic acid itaconic anhydride modified chain extender, a filler and the like. Through the introduction of the triphenylphosphinic acid itaconic anhydride modified chain extender, the material solves the problems of degradation and mechanical property reduction caused by introduction of a filler into a system, and also gives consideration to the flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of modified plastics, and in particular relates to a polycarbonate / polyethylene terephthalate material and a preparation method thereof. Background Art

[0002] PC / PET alloys prepared by blending polycarbonate (PC) and polyethylene terephthalate (PET) have been widely used in many fields such as automobiles, machinery, and home appliances because they can complement each other's strengths.

[0003] In the automotive industry, different manufacturers have put forward requirements for spray painting, dimensional deviation requirements in summer and winter, high modulus, etc., which require material manufacturers to add inorganic mineral powder fillers to PC / PET alloys to enhance their dimensional stability and improve their modulus. However, polyester materials such as PET show low melt strength and melt viscoelasticity during processing, and the processing performance of the material is poor. The alkalinity of inorganic fillers such as talcum powder will degrade the polymer system, greatly increasing the difficulty of material processing. These will lead to a decrease in the impact performance, modulus and other properties of the material. The performance defects introduced during the processing process greatly limit the application of the material in many fields.

[0004] In the polyester processing, the introduction of chain extender modification is a common method to improve the material processability and mechanical properties. Although the addition of commonly used chain extenders can improve this problem, it cannot take into account the degradation problem caused by the introduction of fillers. In addition, under the wave of new energy vehicles, new requirements are also put forward for the flame retardant properties of materials.

[0005] In summary, there is an urgent need for a modifier for flame-retardant PC / PET filling materials to solve the problems of degradation and decrease in mechanical properties caused by the introduction of fillers into the system, while also taking into account the flame retardant properties. Summary of the invention

[0006] In view of the above problems, one of the purposes of the present invention is to provide a polycarbonate / polyethylene terephthalate material, which solves the problems of degradation and reduction of mechanical properties caused by the introduction of fillers into the system, and flame retardant properties.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A polycarbonate (PC) / polyethylene terephthalate (PET) material, comprising the following raw materials in parts by weight:

[0009] 30-80 parts of PC; 10-60 parts of PET; 5-30 parts of triphenylphosphinate-itaconic anhydride-modified chain extender; 5-20 parts of filler; 0-5 parts of processing aid;

[0010] Preferably, the material comprises the following raw materials in parts by weight:

[0011] 50-80 parts of PC; 10-40 parts of PET; 5-20 parts of triphenylphosphinate-itaconic anhydride-modified chain extender; 5-20 parts of filler; 0-5 parts of processing aid.

[0012] In the present invention, triphenylphosphinic acid phosphate is first prepared by a substitution reaction between phosphorus oxychloride and phenylphosphinic acid, and then triphenylphosphinic acid phosphate itaconic anhydride is prepared by a reaction between PH and itaconic anhydride. The schematic diagram is as follows:

[0013]

[0014] The present invention adopts triphenylphosphinate itaconic anhydride as a modifier to be mixed with PC / PET material. The anhydride structure is used as a chain extender component to combine with the multiple binding sites of molecular branching, thereby improving the melt strength and viscoelasticity of the PET material and increasing its molecular weight, which is beneficial to processing while improving the impact performance of the system. In addition, due to the introduction of the phosphine structure, the material can also improve the flame retardant performance, and it is not necessary to achieve a high-efficiency flame retardant effect by additionally introducing a flame retardant. While the phosphoric acid group retained by phenylphosphinate neutralizes the alkalinity brought by the filler, it also weakens the effect of the catalyst in the system, and greatly inhibits the transesterification reaction. The PC / PET material of the present invention has stable formability and good flame retardant and mechanical properties.

[0015] In one embodiment of the present invention, the PC has a melt flow index at 300°C and 1.2 kg of 3-65 g / 10 min, preferably 5-50 g / 10 min, and more preferably 7-35 g / 10 min.

[0016] In one embodiment of the present invention, the intrinsic viscosity of the PET is 0.58-0.87 dl / g. The intrinsic viscosity is measured using a capillary method.

[0017] In one embodiment of the present invention, the filler is an inorganic filler, preferably one or more of montmorillonite, talc, and wollastonite. The above fillers are commonly used in the art, and those skilled in the art can select and determine the amount according to needs.

[0018] In one embodiment of the present invention, the chain extender is triphenylphosphinate itaconic anhydride obtained by the reaction of phosphorus oxychloride, phenylphosphinic acid and itaconic anhydride; preferably, the reaction temperature is 20-50°C and the reaction time is 1-4h. From the composition of the product triphenylphosphinate itaconic anhydride, it can be seen that the theoretical molar ratio of the raw materials phosphorus oxychloride, phenylphosphinic acid and itaconic anhydride is 1:3:3, and those skilled in the art can make adjustments as needed during the actual preparation process.

[0019] In the present invention, the processing aid is selected from one or more of antioxidants, lubricants, ultraviolet absorbers, flame retardants, toughening agents, compatibilizers, light stabilizers, heat stabilizers, metal deactivators, plasticizers, anti-adhesive agents, colorants, coupling agents, nucleating agents, foaming agents, antibacterial agents, mildew inhibitors, acid scavengers, hydrolysis resistant agents, chain extenders, flow modifiers, ester exchange inhibitors, matting agents, antistatic agents, reinforcing agents, fillers, antifogging agents, light diffusers, infrared absorbers, fluorescent brighteners and laser marking agents; preferably, the antioxidant is hindered phenols, phosphites Preferably, the lubricant is one or two or more of fatty alcohols, metal soaps, fatty acids, fatty acid esters, montanic acid and its derivatives, amide waxes, saturated hydrocarbons, polyolefin waxes and its derivatives, silicones and silicone powders, and organic fluorines; preferably, the ultraviolet absorber is one or two or more of benzophenones, benzotriazoles, triazines, benzoates, cyanoacrylates, and phenylimidazoles. The above-mentioned additives are commonly used additives in the field, and those skilled in the art can select and determine the dosage according to needs.

[0020] Another object of the present invention is to provide a method for preparing a polycarbonate (PC) / polyethylene terephthalate (PET) material.

[0021] A method for preparing a polycarbonate (PC) / polyethylene terephthalate (PET) material, wherein the material is the above-mentioned polycarbonate (PC) / polyethylene terephthalate (PET) material, and the preparation method comprises the following steps:

[0022] S1: adding PC, PET, modifier, filler and optional processing aid into a mixer and stirring to obtain a premix;

[0023] S2: The mixture is extruded and granulated through a twin-screw extruder to obtain the target material.

[0024] In the present invention, the temperature of the conveying section of S2 melt extrusion is 230-250°C, the temperature of the plasticizing section is 250-280°C, the temperature of the metering section is 260-280°C, and the screw speed is 200-600rpm. The above process parameters are conventional extrusion process parameters in the art, and those skilled in the art can select them according to needs.

[0025] Another object of the present invention is to provide a use of polycarbonate (PC) / polyethylene terephthalate (PET) material.

[0026] A use of a polycarbonate (PC) / polyethylene terephthalate (PET) material, wherein the material is the above-mentioned material, or is a material prepared by the above-mentioned preparation method, and the material is used as a polycarbonate (PC) / polyethylene terephthalate (PET) material having both mechanical properties and flame retardant properties, and is preferably used in the automotive industry.

[0027] Compared with the prior art, the positive effects of the present invention are:

[0028] The modified material obtained by the present invention ensures the stability of production, effectively inhibits system degradation, obtains high modulus and makes the impact strength reach 65KJ / m 2 , and the flame retardant performance can reach V0. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the infrared spectrum of the synthetic product triphenylphosphinate itaconic anhydride P-PPO-IA-1. DETAILED DESCRIPTION

[0030] In order to better explain the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are only used as illustrations of the present invention and do not limit the description of the present invention.

[0031] The ingredients of the comparative examples and embodiments are as follows:

[0032] Polycarbonate resin: 2070, melt flow index 7g / 10min (300℃, 1.2kg), Wanhua Chemical Group Co., Ltd.

[0033] Polycarbonate resin: 2220, melt flow index 20g / 10min (300℃, 1.2kg), Wanhua Chemical Group Co., Ltd.

[0034] Polyethylene terephthalate resin: CZ-5055, Sanfangxiang Company, with an intrinsic viscosity of 0.68 dl / g;

[0035] Polyethylene terephthalate resin: CZ-328A, Sanfangxiang Company, with an intrinsic viscosity of 0.87 dl / g;

[0036] Phosphorus oxychloride: Adamas Reagent Co., Ltd.

[0037] Phenylphosphinic acid (PPO): Adamas Reagents Ltd.

[0038] Itaconic anhydride (IA): Shanghai MacLean Biochemical Technology Co., Ltd.

[0039] Triethylamine: TEA, Jinan Quansheng Chemical Co., Ltd.

[0040] Ethyl acetate: Sinopharm Chemical Reagent Co., Ltd.

[0041] Talc M05SLC: Mengdu Minerals.

[0042] Montmorillonite (MMT): Sodium montmorillonite, Nanocor, USA.

[0043] Antioxidant: Irganox 168, produced by BASF.

[0044] Diphenyl sulfone sulfonate: KSS, Sinopharm Chemical Reagent Co., Ltd.

[0045] Lubricant: PETS, pentaerythritol stearate, Lonza, USA.

[0046] The performance test is as follows:

[0047] The melt index is tested according to ISO 1133 standard, and the test conditions are: 260℃, 5kg.

[0048] The impact strength is tested according to ISO 179 standard, with specimen size: 80*10*4mm and notch depth 2.0mm.

[0049] The flexural strength was tested according to ISO 178, with a specimen size of 80*10*4mm and a rate of 2mm / min.

[0050] The Vicat softening temperature (VST) was tested according to ISO 306 standard with a load of 50N and a heating rate of 120℃ / h.

[0051] The combustion grade is tested according to UL-94, the specimen size is 130mm*13mm*1.5mm, and it burns vertically.

[0052] The coefficient of linear thermal expansion (CLTE) is in accordance with ISO 11359, the specimen size is 8mm*10mm*3mm, and the test temperature is -45℃~100℃.

[0053] The infrared spectrum test uses a Fourier transform infrared spectrometer, model WQF-600N, and the test wavelength is 4000~400cm in total reflection mode. -1 .

[0054] Preparation of triphenylphosphinate itaconic anhydride:

[0055] Triphenylphosphinic acid phosphate (P-PPO): 85 parts by mass (0.6 mol) of phenylphosphinic acid and 61 parts by mass (0.6 mol) of triethylamine were added to a three-necked flask equipped with a condenser, a thermometer, and a dropping funnel, and 31 parts by mass (0.2 mol) of phosphorus oxychloride were added dropwise. The mixture was stirred continuously at 23°C to allow the substance to react fully. The reaction was continued for 4 hours, and the triethylamine salt was removed by vacuum filtration to obtain P-PPO-1.

[0056] Triphenylphosphinic acid phosphate (P-PPO): 85 parts by mass (0.6 mol) of phenylphosphinic acid and 61 parts by mass (0.6 mol) of triethylamine were added to a three-necked flask equipped with a condenser, a thermometer, and a dropping funnel, and 31 parts by mass (0.2 mol) of phosphorus oxychloride were added dropwise. Stirring was continued at 45°C to allow the substances to react fully. The reaction was continued for 2 h, and the triethylamine salt was removed by vacuum filtration to obtain P-PPO-2.

[0057] Triphenylphosphinate itaconic anhydride (P-PPO-IA): Add 95 parts by mass (0.2 mol) of P-PPO-1, 67 parts by mass (0.6 mol) of itaconic anhydride and an appropriate amount of ethyl acetate into a three-necked flask equipped with a condenser and a thermometer, and continue stirring at 23°C to allow the substances to react fully. Continue the reaction for 4 hours, remove the ethyl acetate by rotary evaporation, and dry in a vacuum oven at 100°C for 5 hours to obtain P-PPO-IA-1.

[0058] Triphenylphosphinate itaconic anhydride (P-PPO-IA): Add 95 parts by mass (0.2 mol) of P-PPO-2, 67 parts by mass (0.6 mol) of itaconic anhydride and an appropriate amount of ethyl acetate into a three-necked flask equipped with a condenser and a thermometer, and continue stirring at 45°C to allow the substances to react fully. Continue the reaction for 2 h, remove the ethyl acetate by rotary evaporation, and dry in a vacuum oven at 100°C for 5 h to obtain P-PPO-IA-2.

[0059] Examples 1-3 and Comparative Examples 1-4:

[0060] The material preparation process is as follows:

[0061] Blending extrusion granulation: Put polycarbonate resin, PET, PPO, IA, P-PPO-IA and M05SLC into a high-speed mixer according to the types and amounts of raw materials in Table 1, and mix and stir. Add the mixture into a loss-in-weight feed scale above the feeding port of the screw extruder, and control the temperatures of zones 1-10 of the twin-screw extruder to 200°C, 220°C, 240°C, 250°C, 250°C, 250°C, 250°C, 240°C, and 235°C, respectively, and the head temperature to 230°C. Control the screw speed to 400rpm, and the mixture undergoes the steps of blending, drawing, water cooling, air drying, pelletizing and drying to obtain a PC / PET composition.

[0062] Comparative Examples 1-4 are compared with Example 2 respectively. Comparative Example 1 is different in that it contains only phenylphosphinic acid, and the others are the same; Comparative Example 2 is different in that it contains only itaconic anhydride, and the others are the same; Comparative Example 3 is different in that itaconic anhydride and phenylphosphinic acid are contained, but only physically blended and added, and the others are the same; Comparative Example 4 is different in that itaconic anhydride and phenylphosphinic acid are not contained, and the common flame retardant KSS is used instead, and the others are the same.

[0063] Table 1 Formulations of Examples 1-3 and Comparative Examples 1-4

[0064] Dosage / weight Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 2150 44.3 24.3 10.3 24.3 24.3 24.3 24.3 2070 35 20 20 20 20 20 20 CZ-328A 2 10 30 10 10 10 10 CZ-5055 8 10 24 10 10 10 10 Antioxidant 168 0.3 0.3 0.3 0.3 0.3 0.3 0.3 PETS 0.4 0.4 0.4 0.4 0.4 0.4 0.4 M05SLC 5 15 / 15 15 15 15 MMT / / 5 / / / / KSS / / / / / / 20 PPO / / / 20 / 10 / I A / / / / 20 10 / P-PPO-IA-1 5 20 / / / / / P-PPO-IA-2 / / 10 / / / /

[0065] Table 2 Performance comparison of Examples 1-3 and Comparative Examples 1-4:

[0066] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Melt index / g / 10min 39 25 45 55 69 50 65 <![CDATA[Impact strength / KJ / m 2 > 30 60 28 15 19 20 15 Flexural modulus / MPa 3200 3700 3200 3300 3100 3300 3300 VST / ℃ 105 114 106 104 100 105 105 CLTE (23~55℃) <![CDATA[55*10 -6 ]]> <![CDATA[45*10 -6 ]]> <![CDATA[55*10 -6 ]]> <![CDATA[55*10 -6 ]]> <![CDATA[60*10 -6 ]]> <![CDATA[55*10 -6 ]]> <![CDATA[60*10 -6 ]]>

[0067] Table 3 Comparison of vertical combustion performance of Examples 1-3 and Comparative Examples 1-4:

[0068] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Combustion level <![CDATA[V2]]> <![CDATA[V0]]> <![CDATA[V0]]> V2 NG <![CDATA[V2]]> <![CDATA[V1]]>

[0069] Note: Combustion level V0>V1>V2>NG.

[0070] By comparing the melt index and VST of Comparative Examples 1-4 and Examples 1-3, it can be found that compared with pure PC / PET alloy, the addition of fillers will cause serious degradation of the material, soaring melt index, and reduced heat resistance. The phosphorous acid in the modifier P-PPO-IA can reduce the antimony catalyst in PET and play the role of an inhibitor. By comparing the mechanical properties of Comparative Examples 1-4 and Examples 1-3, it can be found that the addition of the modifier P-PPO-IA can improve the impact performance of the material. Due to the presence of three branching sites under the same structure, the addition of the same or less content of P-PPO-IA can significantly improve the impact performance of the material, and the impact performance is further improved as the amount of addition increases. By comparing the combustion levels of Comparative Examples 1-4 and Examples 1-3, it can be seen that the addition of PPO alone can improve the flame retardant effect of the material, but the addition of P-PPO-IA can achieve a smaller amount of addition to achieve better flame retardant performance, and is far superior to the effect of conventional flame retardant KSS.

[0071] The above results show that adding the modifier P-PPO-IA to PC / PET filler materials can significantly improve the processability of the materials and enhance their strength, toughness and flame retardancy.

[0072] Those skilled in the art should understand that the present invention is not limited to the above-mentioned embodiments, and that various changes and improvements may be made to the present invention without departing from the spirit and scope of the present invention, and that these changes and improvements are within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A polycarbonate (PC) / polyethylene terephthalate (PET) material, characterized in that: The material comprises the following raw materials in parts by weight: 30-80 PCs; 10-60 parts PET; 5-30 parts of triphenylphosphinate itaconic anhydride modified chain extender; 5-20 parts of filler; 0-5 parts of processing aids; Preferably, the material comprises the following raw materials in parts by weight: 50-80 PCs; 10-40 parts PET; 5-20 parts of a chain extender modified with triphenylphosphinate itaconic anhydride; 5-20 parts of filler; 0-5 parts of processing aids.

2. The material according to claim 1, characterized in that The PC has a melt flow index of 300°C and 1.2kg of 3-65g / 10min, preferably 5-50g / 10min, more preferably 7-35g / 10min; And / or, the intrinsic viscosity of the PET is 0.58-0.87 dl / g; And / or, the filler is an inorganic filler, preferably one or more of montmorillonite, talc, and wollastonite.

3. The material according to claim 1 or 2, characterized in that The chain extender is triphenylphosphinate itaconic anhydride obtained by the reaction of phosphorus oxychloride, phenylphosphinic acid and itaconic anhydride; Preferably, the reaction temperature is 20-50°C and the reaction time is 1-4h.

4. A method for preparing the polycarbonate (PC) / polyethylene terephthalate (PET) material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1: adding PC, PET, modifier, filler and optional processing aid into a mixer and stirring to obtain a premix; S2: The mixture is extruded and granulated through a twin-screw extruder to obtain the target material.

5. Use of a polycarbonate (PC) / polyethylene terephthalate (PET) material, wherein the material is the material according to any one of claims 1 to 3, or is prepared by the preparation method according to claim 4, and the material is used as a polycarbonate (PC) / polyethylene terephthalate (PET) material having both mechanical properties and flame retardant properties, and is preferably used in the automotive industry.

Citation Information

Patent Citations

  • Curing agent capable of retarding flame and reinforcing and toughening epoxy resin, epoxy resin material and application

    CN115536601A

  • Phosphoric anhydride-containing compound and preparation method thereof

    CN116731073A

  • Phosphorus-containing unsaturated polyester resin and resin composition containing the same

    JP2001002769A

  • Novel stable compositions of water and oxygen sensitive compounds and their method of preparation

    US20050288257A1

  • Polymeric alloy material, preparation method therefor, and use thereof

    WO2024066600A1